2005
DOI: 10.1002/hipo.20100
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal stress alters the 5-HTergic modulation to emotional stress at postadolescent periods of rats

Abstract: Several lines of evidence have shown that traumatic events during the early postnatal stage might precipitate long-lasting alteration in the functional properties underlying emotional expression. The aim of the present study was to examine whether the early postnatal stress alters the 5-HTergic mechanism underlying regulation of emotional stress, focusing on the 5-HT(1A) receptor-mediated synaptic responses in adult rats. Pups were exposed to aversive stimulus, footshock (FS) at the postnatal period of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Consistent with previous studies (4,18), fear-related freezing behavior was markedly reduced during CFC retention in the 2wFS group. The low levels of freezing unlikely resulted from deficits in the acquisition of fear conditioning because the expression of freezing immediately after FS conditioning was similar to non-FS controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (4,18), fear-related freezing behavior was markedly reduced during CFC retention in the 2wFS group. The low levels of freezing unlikely resulted from deficits in the acquisition of fear conditioning because the expression of freezing immediately after FS conditioning was similar to non-FS controls.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these findings, the authors suggested that long-term deficits in amygdala function impair fear memory consolidation (17). Interestingly, we also observed that early postnatally stressed animals that received aversive footshock (FS) stimuli during postnatal days 14 to 18 (2nd week FS [2wFS] group) exhibited a marked reduction in freezing behavior during the CFC retention session (4,18). Furthermore, decreases in synaptic transmission in the CA1 field during the CFC retention session did not occur in the 2wFS group (4).…”
Section: Introductionmentioning
confidence: 74%
“…LTP was induced by high-frequency stimulation (HFS: tetanus, 10 trains of stimuli, 10 pulses at 100 Hz, 10-s intertrain intervals) with the same stimulation intensity used for baseline recordings. Tetanus was given at the same intensity as that of the test stimulus (29,30).…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
“…They showed that fear-related freezing behavior observed during exposure to contextual fear conditioning was markedly attenuated in the mouse exposed to aversive stimulus (foot-shock) at the postnatal period of the second week, but not of the third week. The second postnatal week may be the "critical period" for establishing proper behavioral responses to emotional stress in adult rats (Matsumoto et al, 2005). Our present results suggested that the "critical period" should be envisioned for mice, involving the adaptation to emotional stress in the adolescent mice.…”
Section: Discussionmentioning
confidence: 61%
“…7) It is interesting to note that when the stress was applied immediately after weaning, 3 weeks after birth, the mice did not show any changes in the emotion-related behavior during the adolescent period. Lately, Matsumoto et al 9) reported the alteration of the neuronal modulation to emotional stress by early postnatal stress during the postadolescent periods of rats. They showed that fear-related freezing behavior observed during exposure to contextual fear conditioning was markedly attenuated in the mouse exposed to aversive stimulus (foot-shock) at the postnatal period of the second week, but not of the third week.…”
Section: Discussionmentioning
confidence: 99%